Preventing driver error and motorcycle accident causation : - Brooks, Peter (Cranfield University, 1991)
Driver error rather than rider error has been highlighted as a major factor in powered-two wheeler (PTW) accidents. However, little work on understanding and preventing these driver errors has taken place. Previous research which has addressed the issue of driver involvement has focused upon increasing the conspicuity of the PTW or rider and has tended to ignore issues associated with car driver behaviour. A framework is presented which facilitates an understanding of driver error in interactions with PTWs. The concepts of Technical Awareness and Social Awareness are used to describe conditions which may predispose drivers to errors when interacting with PTWs. An empirical examination of the framework is presented, examining the relationship between lack of Technical and/or Social Awareness and accident involvement. Relevant information was obtained from over 700 drivers involved in accidents with PTWs within 9 police divisions in England. This information was compared with responses to a random survey of over 1500 drivers sampled from the same area. The results indicate that some of the most important factors in PTW accidents may be accounted for by lack of driver Technical and Social Awareness. These findings have specific implications for the direction of future research and counter measure development and indicate where previous accident reduction efforts have been lacking. In particular, current emphasis on rider performance and rider conspicuity should be supplemented with direct consideration of drivers. It is concluded that using training and education to increase the Technical and Social Awareness of drivers would be an area of high potential effectiveness.